Back Cover: Two‐Dimensional Sandwich‐Type, Graphene‐Based Conjugated Microporous Polymers (Angew. Chem. Int. Ed. 37/2013). Issue 37 (24th July 2013) - Zhuang, Xiaodong; Zhang, Fan; Wu, Dongqing; Forler, Nina; Liang, Haiwei; Wagner, Manfred; Gehrig, Dominik; Hansen, Michael Ryan; Laquai, Frédéric; Feng, Xinliang
<x xml:space="preserve">Abstract</x> A sandwich is an organic structure consisting of two slices of porous bread separated by a layer of filling. In their Communication on page 9668 ff., X. Feng and co‐workers describe the graphene‐mediated synthesis of two‐dimensional (2D) sandwich‐like conjugated microporous polymers. For the first time, 2D porous carbon materials have been produced directly from this type of sandwich structure without an inorganic porous template.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>